SmartPhones feat SmartMolecules: eBioPhy brings rapid diagnosis to remote locations - Milon, Pohl (2015)
eBioPhy is a diagnostic platform that uses biochemical and biophysical principles together with informatic and communication tools to probe the presence of pathogens in biological samples. The platform aims to bring real-time diagnostics to remote locations where health services are rare and it is based in two main principles: 1) The recognition of pathogens using fluorescently and chemically modified molecules, smart molecules. 2) Data collection and analysis using smartphone capabilities.